Efektivitas Pemberian Puding Kacang Kedelai Dan Rumput Laut Terhadap Kadar Kolesterol Total Pasien Hiperkolesterolemia Di Puskesmas Sekip Palembang - Susyani Susyani; Mika Erlanita Samosir; Manuntun Rotua (Media Kesehatan Politeknik Kesehatan Makassar, 2023)
Hypercholesterolemia is a condition when blood cholesterol levels increase above the normal range (200 mg/dL). Patients with hypercholesterolemia can benefit from reducing risk factors in a number of ways, one of which is by incorporating dietary fiber-based products into the diet. It is known the effect of giving soy bean pudding and seaweed on total cholesterol levels of hypercholesterolemia patients at Sekip Palembang Health Center. This type of research is a quantitative research with a quasi experimental design. The data that has been collected, then analyzed using Friedmant Test analysis, univariate analysis, bivariate analysis, and multivariate analysis. Proximate analysis results of F3 high fiber pudding with 85.55% moisture content, 3.36% ash content, 0.86% fat content, 0.91% protein content, 9.32% carbohydrate content, 7.07 dietary fiber content gram, vitamin C content 4.00 mg, and chemical analysis results niacine content 6.08 mg. The results of the qualitative test of Flavonoids with a sample concentration of 100 g = 100000 µg/ml. There was a significant difference in total cholesterol levels before and after, namely in the treatment group with a p-value 0.05, which was 0,711. Soybean and seaweed pudding containing low fat, high fiber, vitamin C, high niacine and Flavonoids can reduce total cholesterol levels in hypercholesterolemic patients at the Sekip Palembang Health Center. Keywords : Hypercholesterolemia, pudding, soybean flour and seaweed flour, total cholesterol levels